The Factors Related To Community Participation In Household Waste Management - Silfa Amalia; Fajrina Hidayati; Oka Lesmana S; Hendra Dhermawan Sitanggang; Ashar Nuzulul Putra (International Journal of Health Engineering and Technology, 2026)
Community participation in household waste management is a crucial component in maintaining environmental quality and supporting sustainable waste management. This study aims to analyze the level of community participation and examine the relationship between knowledge, attitudes, education, availability of facilities, and the role of community leaders based on Lawrence Green’s theory in Kenali Besar Subdistrict, Jambi City. This research employed a quantitative approach with a cross-sectional design involving 96 respondents selected through purposive sampling. Data were collected using structured questionnaires and analyzed using the chi-square test. The results showed that most respondents had a high level of participation. Significant relationships were found between knowledge (p=0.001), attitudes (p=0.001), education (p=0.001), and availability of facilities (p=0.001) with community participation. However, the role of community leaders was not significantly associated (p=0.406). In conclusion, community participation is influenced by knowledge, attitudes, education, and the availability of facilities. Therefore, efforts to improve participation should focus on continuous education, provision of adequate facilities, and active community involvement.